The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1540-8175.2011.01484.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial‐Mediated Coronary Flow Reserve and Its Relation to Mitral Annular Tissue Doppler Velocities in Offspring of Hypertensive Parents

Abstract: Offspring of hypertensive parents have coronary endothelial dysfunction that appears in response to physiological stimuli (CPT). The coronary endothelial dysfunction is associated with latent LV diastolic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…This discrepancy is probably a result of the differences between measurement of absolute CF values with PET and echocardiographic measurement of CF velocity that has no linear correlation with laminar flow. In fact, previous studies evaluating CF velocity by transthoracic Doppler echocardiography [14,22] or MRI [23] during CPT have found velocity ratios very consistent with the values observed in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…This discrepancy is probably a result of the differences between measurement of absolute CF values with PET and echocardiographic measurement of CF velocity that has no linear correlation with laminar flow. In fact, previous studies evaluating CF velocity by transthoracic Doppler echocardiography [14,22] or MRI [23] during CPT have found velocity ratios very consistent with the values observed in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, increased EAT was associated with poor coronary flow reserve even in patients with angiographically normal coronary arteries [23,24]. In a recent study, Mahfouz et al demonstrated a strong relationship between impaired endothelial coronary flow reserve and left ventricular diastolic dysfunction [25]. Moreover, Sasaki and coworkers reported a positive association between coronary blood flow and isovolumic relaxation time [26].…”
Section: Discussionmentioning
confidence: 98%
“…6 Left atrium (LA) plays a critical role in left ventricular filling with LA reservoir, conduit, and contractile functions. 2,14,15 However, there are not much data with regard to utilization of other advanced techniques such as real-time three-dimensional echocardiographic (RT3DE) imaging in determining LA dynamics, which is a recently developed technique that allows the quantitative assessment of function and volume of any cardiac chamber. [9][10][11][12][13] Abnormal LA function is considered as an early finding in atherosclerosis, which usually accompanies with CSX.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have well documented this association using conventional pulsed and tissue Doppler echocardiographic measurements. 2,14,15 However, there are not much data with regard to utilization of other advanced techniques such as real-time three-dimensional echocardiographic (RT3DE) imaging in determining LA dynamics, which is a recently developed technique that allows the quantitative assessment of function and volume of any cardiac chamber. This technique is considered a feasible and reproducible method for its clinical application.…”
Section: Introductionmentioning
confidence: 99%